Status of Invasive Alien Plant species in Dhankuta Municipality - Shrestha, Saugat (Journal of Research and Development, 2023)
Invasive alien species are plants, animals, pathogens and other organisms that are non-native to an ecosystem, and which may cause economic or environmental harm or adversely affect human health. At least 179 species of alien plant species are naturalized in Nepal and 26 of them have become invasive with negative impacts on environment and economy. Out of 26 invasive alien species four species are among the 100 of the world’s worst invasive alien species. The present study intended to investigate the invasive alien plant species found in Dhankuta Municipality, which has not been explored previously. Present study reported 30 species of invasive alien plant species belong to 13 families of 28 genera. Agro-ecosystems accounted for 40% of the 30 species’ IAPS, followed by grasslands and residential areas (31% each), and forests and shrub-land (27% each).